Suvremena teorija argumentacije: normativna slojevitost svakodnevnih argumenata. - BODLOVIĆ, PETAR (Prolegomena: Journal of Philosophy, 2024)
The paper provides an overview of contemporary argumentation theory, an academic discipline formed in the second half of the twentieth century by focusing on the discipline's historical background, programmatic starting points, research subjects, and methodological tools. The argumentation theory is a heterogeneous discipline characterized, most generally, by logico-epistemological, rhetorical, and dialectical approaches. The historical overview describes the influence of Aristotle, Stephen Toulmin, Chaïm Perelman and Lucie Olbrechts-Tyteca, as well as Charles Hamblin on the formulation and development of the aforementioned approaches. The review of programmatic starting points introduces general pragmatic instructions on how to interpret and investigate arguments and describes the (alleged) limitations of traditional approaches to argument, mostly associated with formal logic. The paper's central part discusses problems and methods of identification, interpretation, analysis, evaluation, and, finally, presentation of the argument. The overview primarily presents the theoretical contributions of dialecticians and informal logicians but also illustrates the practical applications of such contributions by analyzing a real-life argument from the Croatian media (about a possible infection with the coronavirus on Pag).